1996
DOI: 10.1074/jbc.271.12.7072
|View full text |Cite
|
Sign up to set email alerts
|

The Plasmid RK2 Initiation Protein Binds to the Origin of Replication as a Monomer

Abstract: The TrfA protein encoded by the broad host range bacterial plasmid RK2 specifically binds to eight direct repeats (iterons) present at the plasmid replication origin to initiate DNA replication. Purified TrfA protein is largely in the form of a dimer, and using a dimerization test system that involves the fusion of the amino-terminal domain of the cI repressor protein to TrfA, we show that the TrfA protein forms dimers in vivo. Because of the high stability of the dimer form of TrfA, the formation of heterodim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
61
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(61 citation statements)
references
References 47 publications
0
61
0
Order By: Relevance
“…E. coli DnaA, DnaB, DnaC, DnaG primase, DNA gyrase, polymerase III holoenzyme, and SSB proteins are required for RK2 replication in crude extracts (38,39) and in an in vitro replication system reconstituted with purified components. 3 The binding of the TrfA protein to the iterons at the minimal RK2 origin of replication has been characterized in detail (25,26,37,40); however, little is known about the nature of binding of the DnaA protein to oriV. We examined this binding using both the gel mobility shift assay and DNase I footprinting.…”
Section: Resultsmentioning
confidence: 99%
“…E. coli DnaA, DnaB, DnaC, DnaG primase, DNA gyrase, polymerase III holoenzyme, and SSB proteins are required for RK2 replication in crude extracts (38,39) and in an in vitro replication system reconstituted with purified components. 3 The binding of the TrfA protein to the iterons at the minimal RK2 origin of replication has been characterized in detail (25,26,37,40); however, little is known about the nature of binding of the DnaA protein to oriV. We examined this binding using both the gel mobility shift assay and DNase I footprinting.…”
Section: Resultsmentioning
confidence: 99%
“…All TrfA preparations used in the tests were N-terminally histidine-tagged 33-kDa versions of TrfA. The wt TrfA, TrfA F138A, and TrfA ΔLF were purified according to the method of Toukdarian et al (33). E. coli DNA Pol III subunits were a kind gift from M. O'Donnell, The Rockefeller University, New York, NY.…”
Section: Methodsmentioning
confidence: 99%
“…A previous study had shown that although wild type TrfA protein is primarily a dimer in solution, it was the monomeric form that was essential for replication initiation activity (26). Plasmid pGC1 served as the template for the construction of three specific N-terminal deletions and one point mutant as follows.…”
Section: Methodsmentioning
confidence: 99%